Assessment and analysis of agricultural non-point source pollution loads in Henan, China: 2001–2023 - Cangyu Li; Ming Cai; Xinhui Wang (PLoS ONE, 2025)
Agricultural non-point source pollution (ANPSP) is one of the important factors leading to water environmental pollution. Identifying the spatial distribution of ANPSP and implementing regional control measures are, therefore, important for ensuring effective pollution prevention and control. However, analyzing regional ANPSP using a single approach is challenging due to the impacts of geographical, economic, and policy differences. In this context, the present study aims to assess the long-term spatiotemporal characteristics of pollutants and their sources in Henan Province over the 2001–2023 period using inventory analysis, equal standard pollution load method, and cluster analysis. In addition, we investigated the decoupling relationship between ANPSP and agricultural output value using the Tapio decoupling model. The results showed that: (1) distinct variation stages of total pollution, including total emission reduction, structural transition, and emerging conflicts. Specifically, there was a increase in total pollution over the 2001–2006 period, followed by a fluctuation, continuous decrease, and stabilization in the 2007–2013, 2014–2019, and 2020–2023 periods, respectively. The pollution loads of chemical oxygen demand (COD), total nitrogen (TN), and total phosphorus (TP) were reduced by 26.2, 23.5, and 18.2%, respectively. In addition, increases in the contribution rates of livestock and farmland straw. On the other hand, rural households and livestock were the main sources of COD and TP emissions, respectively. The main source of TN emissions has shifted from livestock to farmland straw; (2) the total pollutant load exhibited a distinct spatial distribution pattern. Specifically, the southern part of the study area had the highest pollutant loads, followed, respectively, by the eastern, northern, and western parts; (3) the decoupling relationship between ANPSP emissions and agricultural output values showed fluctuating changes, dominated by weak and strong decoupling status, with gradual improvement. (4) Henan Province was divided into three primary non-point source pollution control zones using cluster analysis, namely high, moderate, and low-risk zones. The high, moderate, and low risk areas had average equivalent pollution indices of 61.89, 40.44, and 15.37, respectively. In this study, we proposed targeted prevention and control measures for ANPSP in Henan Province. These findings provide a reference for the governance and planning of ANPSP in Henan Province, as well as a novel perspective for investigating the relationship between rural development and the environment.